Assessing Potentially Inappropriate Medications in Hospitalized Geriatric Patients in 2 Hospital in Jakarta using STOPP START Criteria - Daniek Viviandhari; Nora Wulandari; Numlil Khaira Rusdi; Nur Rahmi; Nurul Hildayana; Noni Sri Susi Faniroh (Faculty of Pharmacy, Universitas Gadjah Mada)
Geriatric patients have more comorbidities and often receive polypharmacy prescriptions. The prevalence of inappropriate drug use in geriatric patients is in the range of 11.5% - 62.5%. The consequence of polypharmacy is Adverse Drug Reactions (ADR). An effort to reduce the occurrence of medication errors in geriatric patients is the STOPP and START criteria. This study aimed to identify PIMs (Potentially Inappropriate Medications) and PPO (Potentially Prescribing Omission) in geriatric patients according to STOPP / START criteria at Gatot Soebroto Army Hospital and the Jakarta Cempaka Putih Islamic Hospital. This study used a descriptive-analytical method with a cross-sectional design and a prospective data collection method based on analysis of medical records, inpatient installation, and pharmacy installation at Gatot Soebroto Army Hospital in Jakarta on October 2017 and Jakarta Cempaka Putih Islamic Hospital in January 2019. The tool used to collect data in this research was the STOPP START toolkit supporting medication review version 1 2016. The results show that of 85 hospitalized geriatric patients at Gatot Soebroto Army Hospital with the use of 579 drugs, PIMs were present in 8.24% of patients and the prevalence of PPO was 5.88%. Meanwhile, out of 124 hospitalized geriatric patients in Jakarta Cempaka Putih Islamic Hospital with the use of 945 drugs, PIMs were present in 35.48% of patients and the prevalence of PPO was 6.45%. Polypharmacy found to be an independent predictor for PIMs incident.